6x-1/6=9

Simple and best practice solution for 6x-1/6=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-1/6=9 equation:



6x-1/6=9
We move all terms to the left:
6x-1/6-(9)=0
determiningTheFunctionDomain 6x-9-1/6=0
We multiply all the terms by the denominator
6x*6-1-9*6=0
We add all the numbers together, and all the variables
6x*6-55=0
Wy multiply elements
36x-55=0
We move all terms containing x to the left, all other terms to the right
36x=55
x=55/36
x=1+19/36

See similar equations:

| x-16x+3x=180 | | 3/5=2x-6/3+x/5 | | x+30/8=1/4x | | 13z-8z=20 | | -131=22x+45 | | -6x-8=3x+5 | | 4x+1+47=180 | | 3w=-27+12w | | 19-3(a-6)-18=66 | | 6x(-12/3)+4=18/x | | 6(x-3)^2=0 | | (-3-4i)-(-3+5i)=0 | | 4x+3=2x(2x+3) | | Y=3/2x-13/2 | | -30=-8x-14 | | x^2-16x-3x=180 | | 4K-4+3k=5k+16 | | 8-4a=12 | | x^2-1=-x^2+3 | | 116=17+11x | | X+1-4x=-2x-17+6-5x | | 7x+2=-58 | | 3(g+6)=0 | | F(2)=x^2+2x-5 | | x^2-16x+3x=180 | | 3(4x+5)=-31+10 | | 5(3x)-4(2x-3)=4(x+3)+1 | | 17+11z=116 | | 1/4(3x-65)=4x | | 35=105x-16x^2 | | 0.8(x+300)=0.85x-125 | | 2x-24=-32 |

Equations solver categories